Construct Validation of a Novel Hip Fracture Fixation Surgical Simulator. Issue 19 (1st October 2018) - Christian, Matthew William; Griffith, Cullen; Schoonover, Carrie; Zerhusen, Tim; Coale, Max; O'Hara, Nathan; Henn, Ralph Frank; O'Toole, Robert V.; Sciadini, Marcus
Abstract : Introduction: A surgical simulation platform has been developed to simulate fluoroscopically guided surgical procedures by coupling computer modeling with a force-feedback device as a training tool for orthopaedic resident education in an effort to enhance motor skills and potentially minimize radiation exposure. The objective of this study was to determine whether the simulation platform can distinguish between novice and experienced practitioners of percutaneous pinning of hip fractures. Methods: Medical students, orthopaedic residents, orthopaedic trauma fellows, and attending surgeons completed in situ hip-pinning simulation that recorded performance measures related to surgical accuracy, time, and use of fluoroscopy. Linear regression models were used to compare the association between performance and practitioner experience. Results: Notable associations were shown between performance and practitioner experience in 10 of the 15 overall measures ( P < 0.05) and 9 of 11 surgical accuracy parameters ( P < 0.05). Conclusion: This novel simulation platform can distinguish between novice and experienced practitioners and defines a performance curve for completion of simulated in situ hip pinning. This important first step lays the groundwork for subsequent validation studies, which will seek to demonstrate the efficacy of this simulator in improving clinical performance by trainees completing a sequence of skills-training modules.